Ticagrelor or clopidogrel after acute coronary syndrome in the elderly: a propensity score matching analysis from 16 653 patients included in two large multinational registries. (14th October 2021) - Bianco, M; Careggio, A; Biole', C; Quadri, G; Quiros, A; Raposeiras-Roubin, S; Abu-Assi, E; Kinnaird, K; Spirito, A; Templin, C; Nunez-Gil, I; De Ferrari, G M; et al.
Abstract: Background: Higher risk of bleeding with ticagrelor over clopidogrel in elderly patients with acute coronary syndrome (ACS) has been suggested. Purpose: We assessed the incidence of major bleeding (MB), reinfarction (REAMI), and all-cause death in elderly patients to evaluate the safety and efficacy of ticagrelor versus clopidogrel in a population at high risk of bleeding and ischemia treated with percutaneous coronary intervention (PCI). Methods: RENAMI and BleeMACS, real-world registries of patients with ACS who underwent PCI and received dual antiplatelet therapy, were merged. The pooled cohort was divided into two groups, clopidogrel versus ticagrelor and propensity score matching (PSM) analysis performed. Statistical analysis considered two age groups (<75 versus ≥75 years). Endpoints were BARC 3–5 MB, REAMI and all-cause death at 1 year. Independent risk factors of MB were identified. Results: The study included 16, 653 patients (13, 153 <75 and 3, 500 ≥75 years). Ticagrelor was underused in elderly patients (16.3% versus 20.8%, P<0.001). Using PSM, two treatment groups of 1, 566 patients were included in the final analysis. Ticagrelor appeared to prevent REAMI (hazard ratio [HR], 0.31; 95% confidence interval [CI], 0.2–0.6; P<0.001) and all-cause death (HR, 0.60; 95% CI, 0.4–0.9; P=0.026) irrespective of age. In patients ≥75 years, ticagrelor increased the incidence of MB compared with clopidogrel (HR, 1.49; 95% CI, 0.70–3.0; P=0.257) without statistical significance; ticagrelor was found to significantly reduce all-cause death (HR, 0.32; 95% CI, 0.1–0.8; P=0.012) and REAMI (HR, 0.25; 95% CI, 0.1–1.1, P=0.072) without statistical significance. Multiple Cox regression revealed that age (HR, 1.03; 95% CI, 1.02–1.05; P<0.001) was an independent risk factor for bleeding, whereas hemoglobin level was inversely proportional to bleeding (HR, 0.80; 95% CI, 0.72–0.88; P<0.001). Conclusions: Ticagrelor did not significantly increase MB compared with clopidogrel in elderly patients hospitalized for ACS and treated with PCI, significantly improving 1-year survival. Further studies on elderly patients are required. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Astra Zeneca